Kontrol Sosial Orang Tua Tunanetra Terhadap Anaknya Di Kota Pekanbaru - Ummi Asomah; Hesti Asriwandari (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This research is motivated by how visually impaired parents exercise social control over their sighted children in the city of Pekanbaru. The research aims to understand the process of conveying values and to identify the obstacles and sanctions imposed by visually impaired parents in their social control of their children. The study utilizes a qualitative approach, with data collection techniques involving interviews and observations. Subject selection for the research employs a purposive method with a snowball technique. Visually impaired parents play a crucial role in guiding the behavior and development of their children. Despite their physical limitations, visually impaired parents demonstrate a high level of concern and commitment to the education, household chores, and religious practices of their children. Effective social control by visually impaired parents over their children occurs when the values are effectively conveyed. If the values are not effectively conveyed, obstacles may arise, and these obstacles can be addressed through the imposition of sanctions to maintain control.